Perancangan Struktur Beton Bertulang Bangunan Hotel 9 Lantai Tahan Gempa di Kota Palembang Berdasarkan SNI 1726:2019 dan SNI 2847:2019 - Asharul Khafi; Sapta Sapta; Sari Farlianti (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study discusses the design of reinforced concrete structures in an 8-story hotel building with 1 roof floor using a Special Moment Resisting Frame System (SRPMK). The design refers to the provisions of SNI 2847:2019 and SNI 1726:2019. The building has dimensions of 54 x 16.2 m with a total height of 27.8 m. The materials used are 30 MPa concrete and 420 MPa reinforcement steel. The research method was carried out by comparing the analysis results assisted by ETABS software with the provisions applicable in SNI 2847:2019 and SNI 1726:2019. The structural analysis results show that the building meets the strength, stiffness, and ductility requirements in accordance with SNI 2847:2019 and SNI 1726:2019. In conclusion, the design of this hotel is safe and complies with the provisions of SNI 2847:2019 and SNI 1726:2019.